Linking past and future research in tourism management through the lens of marketing and consumption: a systematic literature review - Irina Saur-Amaral; Pedro Ferreira; Rosa Conde (Tourism & Management Studies)
We perform a systematic literature review on academic papers in tourism marketing and consumption in ISI Current Contents. Based on 617 academic papers from 2001 to date, we perform content analysis in a grounded-theory methodological approach and map the field of tourism marketing and consumption, identifying main schools of thought (invisible colleges) and main players. We see a tendency to increase publications in 2007 and later in 2009. We identify key areas that developed in the most recent years and “dying areas”, emphasizing possible trends towards publications in tourism marketing and consumption in the coming years. We point out specialized international journals in this area (Tourism Management leads the game, by far, but also International Journal of Contemporary Hospitality Management, Service Industries Journal, and Journal of Business Research are well positioned). Results benefit researchers in tourism management that wish to strategically focus their research in order to maximize publication and impact. They also benefit entrepreneurs/practitioners that wish to understand the expected evolution of the tourism management from an academic perspective, so as to subsequently develop more effective policies.